Protein and thiamin intakes are not related to cognitive function in well‐nourished community‐living older adults. Issue 1 (5th March 2015) - Koh, Freda; Charlton, Karen E.; Walton, Karen; Brock, Erin; McMahon, Anne T.; Langford, Kelly; Host, Alison; Crowe, Ruth; Thornhill, Kayla
Abstract Aim Some studies have suggested that thiamin (vitamin B1) may have a protective effect on the maintenance of cognitive function in older people. The aim of this exploratory study was to investigate the association between dietary intakes, specifically protein and thiamin with cognitive function. Methods A cross‐sectional analysis was conducted on community‐living older adults aged ≥60 years in the Illawarra region of New South Wales. Dietary intakes were collected using a three‐day food record and various domains of cognition were tested. Depressive symptoms were assessed using the Geriatric Depression Scale (GDS). Correlations and regressions were conducted to investigate the association between dietary intakes and areas of cognitive function. Results Forty‐eight volunteers participated (mean age: 78.2 ± 6.1 years; BMI: 28.8 ± 5.4 kg/m2; MNA Score: 26.8 ± 2.4; 35% men). Men had higher intakes of energy (kJ), carbohydrate, saturated fat and sodium than women. No significant association was found between protein or thiamin and the tested domains of cognition. Associations were found between vitamin D intake and the Letter Fluency Test (r = −0.302, P < 0.05) and Rey Auditory Verbal Learning Test (r = −0.400, P < 0.001), and between both carbohydrate (r = 0.383, P = < 0.05) and iron intake (r = 0.333, P < 0.05) and the GDS. Conclusions In a sample of generally healthy, well‐nourished older adults, no associations were found between protein or thiamin intakes and the tested components of cognition. Further investigation is required to determine if an increase in these nutrients through the provision of food sources has benefits to improve cognitive function.